Physicochemical and melissopalynological profiles of Citrus limon honey from Tucumán-Argentina. Hesperidin as a suitable marker of floral origin - Maldonado, Luis Maria (2021)
Geographical Indications (GI) are tools used to add value, protect and recognize the differentiated quality of a product as a consequence of environmental and territorial influence. The objective of this work was to determine physicochemical, melissopalynological and sugar profiles plus chemical markers of Citrus limon monofloral honey produced in Tucumán-Argentina, to the development of the GI “Lemon blossom honey from Tucumán”. Samples harvested between August and October 2016, 2017 and 2018 were analyzed. It was established that in addition to Citrus limon, the most frequent pollen species was Salix type. This honey is very light in color (≤ 30 mm Pfund), slightly acidic (≤ 20 meq.kg-1), with moisture values from 15 to 19 g/100g, low diastatic activity (≤ 27 Gothe units), HMF (≤ 3.0 mg.kg-1) and electrical conductivity (≤ 0.32 mS.cm-1). Color inversely correlates with the amount of Citrus limon pollen. The sugar profile showed a higher fructose content than glucose, sucrose and maltose, and intermediate tendency towards crystallization. Hesperidin was easily detected and quantified in all samples. The content of methyl anthranilate was much lower than the international reference for citrus honeys and also, was not detected in some samples. Hence, should be a complementary indicator and hesperidin could be used instead as a chemical marker of genuineness.